"Beginning to Belong" Emerging pre-professional Identity among Community College Fieldwork Students: A Theoretical Framework for Aspiring Social Workers. Issue 5 (20th October 2022) - Spector, Anya Y.
ABSTRACT: Community college human services students comprise a significant number of nascent and future professionals for the social services and social work workforce. An associate degree in human services prepares students either to enter this workplace or to begin a four-year college program. Regrettably, these important future providers are overrepresented among students affected by economic and social inequality. They are often young, first-generation-to-college students, and have limited professional experience. Developing a sense of professional identity can help these students prepare for a career and achieve academic success. While professional identity development among senior level and graduate social work students is well studied, there is a paucity of research with respect to community college students in the human services, leaving a gap in our understanding of best practices for pedagogy that would support their social work aspirations. This study helps to fill this gap by proposing a theoretical framework for professional identity adapted from Barretti's Professional Socialization Model and based on 40 qualitative reflective journal entries from community college students in field placement.